Edukasi dengan Media Permainan Inisiatif Si Kancil Meningkatkan Kesiapsiagaan Siswa dalam Menghadapi Bencana - Putu Susy Natha Astini; Ni Luh Putu Yunianti Suntari Cakera; Ayu Resita Pradnyadewi (Jurnal Gema Keperawatan, 2017)
The aim of this research is to know the effect of educational learning through “Inisiatif Si Kancil” game towards  elementary students’ awareness in encountering disaster. The type of this research is Pre-Experimental Design with One-Group Pretest-Posttest design using Simple Random Sampling. There are 57 samples and the result showing that the awareness before the student was given an awareness education is are (31.6%) student who was aware and after they were given the education are 33 (57.9%) student are aware. The numbers of aware student is increasing after the giving of education. The result of this research has been tested using Wilcoxon statistic test. The p-value = 0.000 alpha (0.05), hence, there are effect occurred of the awareness education given to the student through “Inisiatif Si Kancil” game in SDN 3 Serangan Denpasar.